Comprehensive evaluation of the oxidative gas based aging method for loose asphalt mixtures. (17th October 2022) - Sreeram, Anand; Adwani, Dheeraj; Arras, Benjamin; Blomdahl, Daniel; Misztal, Pawel; Bhasin, Amit
Highlights: Use of Vocus PTR-TOF spectrometer to investigate accelerated aging mechanisms of binders. Formation of oxygenated species significantly higher under oxidative gas-based environment as compared to air. Upscaling of an oxidative gas based aging method for the large-scale evaluation of loose mixtures. Mixture and binder results indicate the clear effectiveness of the developed approach. Abstract: The simulation of field aging using laboratory techniques is an essential prerequisite in the design of high-quality asphalt mixtures. Previous studies in this area have indicated the potential to use an accelerated method for aging loose mixtures using highly oxidative gases, namely ozone and other reactive oxygen species (ROS). Based on that, the present work was concerned with the investigation of the accelerated aging mechanisms in effect and upscaling of the experimental setup to accommodate larger quantity of mixes. Firstly, the chemical transformations and real time oxidation products formed under an ozone rich environment were compared to an air-based environment for three binders using a Vocus proton transfer reaction (PTR-TOF) time-of-flight mass spectrometer. It was observed that the formation of oxygenated species was significantly higher under an ozone rich environment, indicating higher levels of oxidation. The high-resolution level characterization of the oxidation series of several different molecules provided definitive evidence to support the previous hypothesis of using ozone and ROS to fast-track the oxidation of asphalt mixtures. Following this, an experimental method was developed to age up to nine kilograms (kg) of loose mixtures obtained from a mixing plant using ozone and ROS, in a duration of 22 h. After aging, different properties of the mixtures were compared to analogous mixtures aged as per a benchmark method of loose mixture aging at 95 °C for 5 days in a laboratory oven. The various results obtained from the IDEAL-CT tests, rheological and chemical property analyses of extracted binders clearly illustrated the effectiveness of the oxidative gas based aging method for the accelerated aging of loose mixtures, providing comparable levels of aging as traditional methods. Overall, the work conducted in this study provides comprehensive results regarding critical aspects of the developed method and alludes to the opportunity for wide scale applicability.